2007
DOI: 10.1016/j.brainres.2007.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate-dependent induction of reactive astrogliosis and cell death in three-dimensional neuronal–astrocytic co-cultures

Abstract: A mechanical insult to the brain drastically alters the microenvironment as specific cell types become reactive in an effort to sequester severely damaged tissue. Although injury-induced astrogliosis has been investigated, the relationship between well-defined biomechanical inputs and acute astrogliotic alterations are not well understood. We evaluated the effects of strain rate on cell death and astrogliosis using a three-dimensional (3-D) in vitro model of neurons and astrocytes within a bioactive matrix. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 55 publications
6
112
0
1
Order By: Relevance
“…12,[18][19][20][21][22] Recently, we developed a 3D collagen gel model for studying astroglial biology that has significant advantages over standard 2D models, allowing astrocytes to behave in a way much more reminiscent of their in vivo counterparts. 23 Since 3D culture systems can allow mechanical cues to be isolated from chemical cues, 24 we have adapted our 3D culture model in this study to explore the effect of astrocyte alignment on neurite growth.…”
mentioning
confidence: 99%
“…12,[18][19][20][21][22] Recently, we developed a 3D collagen gel model for studying astroglial biology that has significant advantages over standard 2D models, allowing astrocytes to behave in a way much more reminiscent of their in vivo counterparts. 23 Since 3D culture systems can allow mechanical cues to be isolated from chemical cues, 24 we have adapted our 3D culture model in this study to explore the effect of astrocyte alignment on neurite growth.…”
mentioning
confidence: 99%
“…It was reported a strain rate of larger than 10 (1/s) caused damage to axons (3) (5) (7) , therefore, the strain rate obtained from the impact experiment was large enough to damage the cell. LaPlaca et al (7) gave a load to the cultured cells in which the strain was 50% and the strain rate was 30 (1/s), and observed approximately 20% cell mortality. When mortality of cells in this study was 20%, the strain was 0.2% and the strain rate was 19.02 (1/s).…”
Section: Discussionmentioning
confidence: 99%
“…Laplaca et al cultured cells in a gel and generated 3D deformation of the cells by producing a shear deformation of the gel (strain < 50%, strain rate < 30/s). Neuronal cells showed a lower tolerance to this strain than the glial cells (LaPlaca et al, 2005;Cullen et al, 2007).Tamura et al analyzed the difference in strain caused by a tensile test between porcine brain tissue and nerve fiber in the white matter, and reported that the maximum neural fiber strain was ~25% of the level in the surrounding tissue (Tamura et al, 2006). Nakayama et al showed morphological changes of axons and the progress of this damage over time caused by one-dimensional, horizontal oscillations of nerve cells (Nakayama et al, 2001).…”
Section: The Mechanism Of Daimentioning
confidence: 99%